Spontaneous transvaginal evisceration: a case of recurrence - Ribeiro, Susana Perdigão (BMJ Case Rep, 2016)
Vaginal evisceration can be defined as a defect in the vaginal wall resulting in prolapse of the intraperitoneal contents. This is a rare complication of hysterectomy, but may result in severe morbidity. We report the case of a postmenopausal woman with transvaginal evisceration of the sigmoid colon 1 year after an abdominal hysterectomy. An exploratory laparotomy was undertaken to reduce the prolapsed sigmoid colon through a combined vaginal-abdominal route. Repair of the defect of the vaginal vault was made using an absorbable running suture. Two years later, the patient presented at the emergency department with a transvaginal evisceration of the omentum. An exclusively vaginal approach was then chosen to repair the smaller vaginal defect and vaginal cuff was closed using non-absorbable sutures. As two different surgical approaches were used in this patient, a discussion of the different treatment options and also of the principles of prevention of vaginal cuff dehiscence is provided.